2019
DOI: 10.2174/1573401313666170823160217
|View full text |Cite
|
Sign up to set email alerts
|

Shilajit (Mumie): Current Status of Biochemical, Therapeutic and Clinical Advances

Abstract: Background: Shilajit (mumie), a natural multi-component herbomineral ethnomedicinal food, is used as a traditional medicine for enhancing the quality of life and for management of health ailments in many countries of the world. Use of Shilajit as an adaptogen, aphrodisiac, rejuvenator and anti-aging substance is mentioned in many ancient texts. This review aims to provide comprehensive insights into its biochemical aspects, microbial role in biosynthesis, bioactivities and to establish correlation between trad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 79 publications
0
17
0
Order By: Relevance
“…They are very similar to humic acids, differentiated by oxygen and carbon contents, degree of polymerization, acidity, inter-mediate molecular weight and color (26). Traditionally, fulvic acid is used for brain-related disorders such as Alzheimer's diseases, respiratory tract infections, fatigue, heavy metal toxicity, preventing hypoxia and is well studied for its effect on immune health and reducing inflammation (27,28). It serves as an important vehicle that carries nutrients and vitamins to the exact place in our bodies (29).…”
Section: Properties Of Humic Substancesmentioning
confidence: 99%
See 1 more Smart Citation
“…They are very similar to humic acids, differentiated by oxygen and carbon contents, degree of polymerization, acidity, inter-mediate molecular weight and color (26). Traditionally, fulvic acid is used for brain-related disorders such as Alzheimer's diseases, respiratory tract infections, fatigue, heavy metal toxicity, preventing hypoxia and is well studied for its effect on immune health and reducing inflammation (27,28). It serves as an important vehicle that carries nutrients and vitamins to the exact place in our bodies (29).…”
Section: Properties Of Humic Substancesmentioning
confidence: 99%
“…Selenium induces immunity by enhancing the growth and activity of T lymphocytes and other immune-competent cells (54). It has also been shown that deficiency of Selenium has a negative impact on immune cells during activation, cell differentiation, and cell proliferation (27). The evidence of immuno-stimulatory effect determined by NK cell activity, T cell proliferation, innate immune cell functions have been documented (55,56).…”
Section: Seleniummentioning
confidence: 99%
“…HSs have been used for thousands of years in human healthcare. Humic substances are well-known drugs in Indian Ayurvedic medicine as “shilajit” [ 17 , 18 , 19 , 20 ] since time immemorial. They were also used in European mud- and balneotherapy from ancient times [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have also shown that Shilajit contains some amount of ellagic acid, albumins, triterpenes fatty acids, gums, and aromatic carboxylic acids. Some pharmacological activities that have been linked to Shilajit include anti-inflammatory activity, antidiabetic analgesic, spermatogenic and orogenic, anti-fungal, radioprotective, anti-oxidant, immunomodulatory, and anti-viral properties (Mishra et al, 2019;Ezhilarasi et al, 2020). MLH1 (mutL homolog 1) is a gene that functions in the provision of instruction for the synthesis of the proteins involved in the repair of damaged genes.…”
Section: Introductionmentioning
confidence: 99%